Do home visiting programmes improve children's language development? A systematic review. (September 2020) - Henwood, Tom; Channon, Sue; Penny, Helen; Robling, Mike; Waters, Cerith S.
Highlights: This systematic review explores the impact home visiting programmes can have on language development in young children. The review found that by no means do all Home Visiting Programmes look at child language development as an outcome. Study comparison showed that children's language outcomes vary, as to the range of assessment tools used by studies. We consider what programme model factors create opportunities for positive impacts upon children's language development. Abstract: Objectives: This review examines home visiting programmes that specifically provide home based support to vulnerable, socially disadvantaged women who are either pregnant or have recently become a new parent. Home visiting programmes often report multiple outcomes. The purpose of this review is to systematically summarise how effective home visiting programmes are at improving young children's language development. Data sources: A comprehensive search of four online databases (Embase, Emcare, Psycinfo and Medline) between 1990 and 2020 was conducted, as well as a hand search of the references of relevant studies. Review method: Studies were screened with N  = 11 meeting the inclusion/exclusion criteria. The risk of bias of each study was assessed. To enable comparisons between home visiting programmes, relevant data was extracted using an adapted version of the Cochrane Public Health Group Data Extraction and Assessment Template. Results: Most of the home visiting programmes had been established in America. Six of the eleven studies reported positive language outcomes for children. Where statistical data was reported, the magnitude of the difference between the intervention and control groups represented small effect sizes. Nine different language measures were used, reporting on varying domains of language development rendering comparisons across programmes difficult. Most studies failed to report the duration of home visits, though studies which started prenatally showed the most promise in improving children's language development. Conclusion: Home visiting programmes targeted at socially disadvantaged women and their children have the potential to positively influence the language development of the child. This review highlights that not all home visiting programmes measure the impact that the programme has on children's language development, and not all home visiting programmes achieve positive language outcomes. Initiating visits prenatally may help towards the improvement of children's language development. Future evaluations of home visiting programmes should explore this finding further, consider the language assessment tools selected, and improve on the reporting of their language results.